Dal laboratorio Antigone al laboratorio Theano Pitagorica. Un’esperienza Sui Generis - Montepaone, Claudia; Pelosi, Maria Letizia; Grimaldi, Aurora (B@belonline, 2024)
The Antigone Laboratory, founded in 2004, has been an influential institution in the field of gender studies. Its interdisciplinary approach includes in-depth group discussions, direct textual analysis, and a critical examination of gender perspectives throughout different historical periods. The laboratory fosters an environment of open dialogue among scholars, instructors, and students, providing a platform for sharing diverse educational experiences and insights.